PROFILE OF TEACHERS' TEACHING SKILLS IN SOCIAL EMOTIONAL ASPECTS IN THE ERA OF INDEPENDENT CURRICULUM IN ELEMENTARY SCHOOLS - Ida Sanjaya Sanjaya; Ganes Gunansyah; Ari Metalin Ika Puspita (Universitas Majalengka, 2025)
This study aims to find out in depth the profile of teachers' teaching skills in the Social Emotional dimension in the era of the Merdeka Curriculum for Elementary Schools and is expected to contribute significantly through a more thorough understanding of teachers' readiness to implement the Social Emotional dimension in the era of the Merdeka Curriculum. This research uses a qualitative approach. The research subjects consisted of first grade teachers and fifth grade teachers at UPT SDN 339 Gresik. The teaching skills of teachers in the Socio-Emotional aspects of the Merdeka Curriculum era in the aspect of self-awareness in the high grade score 12.5 (62.5%) category are sometimes seen, the low grade score 8.5 (42.5%) category is rarely seen. The self-management aspect of the high class score 16.5 (66%) is sometimes seen, the low class score 11.5 (46%) is rarely seen. The social awareness aspect of the high class scored 26 (74.3%) in the often seen category, the low class scored 19.5 (55.7%) in the sometimes seen category. The aspect of relationship skills of the high class scored 31.5 (70%) in the often seen category, while the low class scored 22.5 (50%) in the sometimes seen category. The aspect of Responsible Decision Making in the high class scored 7 (46.7%) in the rarely seen category, while the low class scored 6 (40%) in the rarely seen category. Emotional social skills in low grade teachers are better than high grade teachers, although the percentage of 74.3% is the highest percentage of the maximum 100%, only obtained in the aspect of social awareness. The impact of this research is the urgent need for teacher professional development related to improving Social Emotional Competence, especially for high grade teachers so that there is no gap in application at all grade levels.